Researcher mobility and cooperation in the science system - Maria Karaulova; Henning Kroll; Cecilia Garcia Chavez; Hendrik Berghäuser (Expertenkommission Forschung und Innovation (EFI), 2024)
This study covers two topics: (1) the analysis of international inventor mobility and cooperation with the focus on Germany; (2) a mobility analysis for researchers in critical career positions in the German research system (professors in German universities, directors of non-university public research organisations, European Research Council and Emmy Noether grant holders). The study of inventor mobility was informed by a literature review. Transnational patent applications in the database PATSTAT in the period of 2000-2020 were analysed. The findings indicate that more inventors leave Germany than come here, however, Germany is an important connecting hub in the international inventor mobility network. The mobility analysis for researchers in critical career positions uses scientific publications in the Scopus database during the years 2005-2021. The results show that international researchers are represented among the critical groups and constitute an important source of talent in the German science system.
Keywords: 330